PENGEMBANGAN MODEL PEMBELAJARAN IMPROVISASI IMAJINATIF DALAM PEMBELAJARAN KONVERSI CERPEN KE DALAM BERMAIN PERAN SISWA SMA KELAS XI - Risdiawati, Dian (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
The purpose of this research and development is to produce Imaginative Improvisation Learning Model in the conversion short story to role play learning. Imaginative Improvisation Learning Model Â is a way of learning that is planned to make students easier to modify short story texts into role play so that learning can take place actively, effectively, and creatively. The steps of the Imaginative Improvisation learning model, are (1) developing a framework, (2) improvising dialogue, (3) improvising behavior, and (4) assessment. Imaginative Improvisation learning model is a model that converts into role play by developing students' imagination and spontaneity. The data collectable by questionnaire from language and literature expert, model learning expert, Indonesian Language teacher, and student. Based on test product result, it is known that the product reaches a valid category and can be implemented.The purpose of this research and development is to produce Imaginative Improvisation Learning Model in the conversion short story to role play learning. Imaginative Improvisation Learning Model Â is a way of learning that is planned to make students easier to modify short story texts into role play so that learning can take place actively, effectively, and creatively. The steps of the Imaginative Improvisation learning model, are (1) developing a framework, (2) improvising dialogue, (3) improvising behavior, and (4) assessment. Imaginative Improvisation learning model is a model that converts into role play by developing students' imagination and spontaneity. The data collectable by questionnaire from language and literature expert, model learning expert, Indonesian Language teacher, and student. Based on test product result, it is known that the product reaches a valid category and can be implemented.